PENERAPAN MOTION TWEEN UNTUK ANIMASI DUA DIMENSI RUTE PERJALANAN BUS TRANS JOGJA - Nugrahenny, Dwi; Honggowibowo, Anton Setiawan; Mukti, Mega Lesya (SENATIK STT Adisutjipto, 2013)
Transportation  is  one  of  the  important  aspects  in  a  region,  where  public transportation  take  effect  on  the  mobility  of  the  people.  To  achieve  a  good transportation can be create, so that the infrastructure and other supporting factors are  needed. Yogyakarta municipality  area  has  a lot  of  public transportasion,  one  of them  is  “Trans  Jogja”  bus,  where  each  bus  line  has  its  route  to  reach  any destination.  It  is  needed  a  supporting  media  that  can  provide  information  about  the route for each bus line so that people can be easily deciding which bus line that can use to reach their destination. Those information presented in the form of animation with  an  interesting  and  informative  media.  The  use  of  animation  as  an  information media  that  shown  as  a  route  trip,  bus  line  including  bus  stop  and  departing passangers  place  assessed  can  be  use  as  one  of  the  other  option  for  obtaining information except from a conventional map.